'Lost in translation' : learning outcomes and the governance of education - Lassnigg, Lorenz [Verfasser] (My University, 2012)
"This paper gives a critical assessment of the relationship between learning outcomes and the governance of education and training systems. Learning outcomes are defined as an instrument that might work at different levels with different meanings and different results: at the level of education and training practice, they might obtain pedagogical results, at the level of policy-making they might contribute to the governance of education and training. However, the ways in which governance impacts on pedagogy is called into question; in particular the argument challenges the assumption of a straightforward and successful 'top-down'-relationship between governance and pedagogy. First, an assessment is undertaken into supportive and critical expectations about learning outcomes: of what they should achieve and of what is deemed necessary to make them work on the one hand and of detrimental effects they might have, on the other. Second, a framework for the analysis of the impact of learning outcomes is proposed; this brings some approaches from the literature together in a systematic fashion and is also used to interpret some developments of the use of learning outcomes in Austria and in other countries. As a result, we conclude that most expectations of the learning outcomes approach are overstated, as are critiques. Evidence shows that there might be pedagogical benefits of learning outcomes if they are properly implemented; however, they appear too weak as an instrument to bring about the desired results as a governance device. They might successfully change policies, however, without having the desired impact on education and training practice." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 4.3 Steuerung; I 2.2.1 Westeuropa; I 2.2 Europa; Lernergebnisorientierung; Bildungssteuerung; Beschäftigungsfähigkeit; Österreich; Europa